High-temperature anti-oxidation FeCrAlSiNb coating and preparation method thereof

By introducing Si and Nb elements into the FeCrAl coating and using ion beam-assisted magnetron sputtering technology and annealing treatment, the problem of the surface protective oxide layer of the FeCrAl coating not being formed quickly enough at high temperatures, significantly improving the high-temperature oxidation resistance and mechanical properties of the coating.

CN120193241APending Publication Date: 2025-06-24CHONGQING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510522557.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2025-06-24

AI Technical Summary

Technical Problem

The existing FeCrAl coating does not form a surface protective oxide layer at high temperatures quickly enough, resulting in interdiffusion between the zirconium alloy matrix above 950°C, forming Fe-Zr eutectic, resulting in a decrease in film-based bonding strength and causing the coating to peel off.

Method used

By introducing Si and Nb elements into the FeCrAlSiNb coating, and using ion beam-assisted magnetron sputtering technology to prepare the coating. Combined with an annealing treatment of 650°C to 850°C, the redistribution of coating elements and the reaction between Si and Zr is promoted to form a high-intensity zirconium silicide diffusion layer.

Benefits of technology

It effectively promotes the rapid generation of protective oxide layer on the surface of the coating, improves the binding force between the coating and the substrate, inhibits the interdiffusion of Fe-Zr elements, and significantly improves the high-temperature oxidation resistance and mechanical properties of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005374405930000071
    Figure BDA0005374405930000071
  • Figure BDA0005374405930000072
    Figure BDA0005374405930000072
  • Figure HDA0005374406080000011
    Figure HDA0005374406080000011
Patent Text Reader

Abstract

The invention discloses a high-temperature anti-oxidation FeCrAlSiNb coating and a preparation method thereof. The preparation method comprises the following steps: S1, etching a target material and a substrate; s2, a FeCrAlSiNb high-entropy alloy coating is deposited, specifically, the atmosphere and the air pressure of the vacuum chamber are kept unchanged, the FeCrAlSiNb high-entropy alloy coating is deposited through the magnetron sputtering technology, the direct-current sputtering power is 80-120 W, and the deposition time is 8-12 h; an alloy coating is obtained on the surface of the base body; and S3, annealing treatment is conducted, specifically, atmospheric annealing treatment is conducted for 30-40 min at the temperature of 650-850 DEG C. After annealing treatment, an obvious Si-Zr diffusion zone is formed between the FeCrAlSiNb coating and a matrix, a complete and continuous thin oxide layer is generated on the surface of the coating, the mechanical property is improved, meanwhile, the excellent high-temperature oxidation resistance characteristic is presented, and more choices are provided for accident fault-tolerant nuclear fuel cladding materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alloy coating materials, and particularly relates to a high-temperature oxidation-resistant FeCrAlSiNb coating and a preparation method thereof. Background Art

[0002] Zirconium (Zr) alloys have advantages such as low neutron absorption cross-section, high corrosion resistance, and good wear resistance, and are widely used as nuclear fuel cladding materials for light water reactors (LWRs). However, the severe oxidation and significant heat generation of Zr-based alloys in a high-temperature steam environment will significantly increase the explosion risk caused by hydrogen in nuclear reactor accidents. Therefore, there is an urgent need to develop accident-tolerant fuels (ATF) claddings that are environmentally reliable and corrosion-resistant with a high safety margin. Preparing a coating on the surface of a zirconium alloy cladding has the characteristics of simplicity, no change in the operating conditions inside the nuclear reactor, and inheritance of the excellent properties of the zirconium alloy, and has become the most economical and rapid effective way for current ATF.

[0003] High-entropy alloy (HEA) coatings have excellent properties such as high mechanical strength and high-temperature oxidation resistance due to the four major effects of high-entropy alloys, and have great potential and possibility as accident-tolerant nuclear fuel cladding coatings. FeCrAl coatings have good high-temperature oxidation resistance because they can form a protective oxide layer on the material surface during oxidation, and are one of the candidate materials for ATF. However, research shows that the high-temperature oxidation resistance of FeCrAl coatings depends on the rapid formation of a surface protective oxide layer, and above 950 °C, the Fe-Zr eutectic formed by the interdiffusion between FeCrAl and zirconium alloy will cause a significant decrease in the film-substrate bonding strength, resulting in coating peeling. Element doping can promote the formation of an oxide layer on the coating surface through the interaction between elements and inhibit the element diffusion between the coating and the substrate, which is one of the simplest and most effective methods to improve the high-temperature oxidation resistance of the coating. FeCrAl-based coatings may have good high-temperature oxidation resistance while possessing the excellent mechanical properties of HEAs coatings, providing more choices for accident-tolerant nuclear fuel cladding materials. Currently, there is a lack of excellent ATF cladding materials on the market. Summary of the Invention

[0004] The purpose of the present invention is to address the above problems and provide a high-temperature oxidation-resistant FeCrAlSiNb coating and a preparation method thereof.

[0005] In order to achieve its purpose, the present invention adopts the following technical solutions:

[0006] The first aspect of the present invention provides a preparation method for a high-temperature oxidation-resistant FeCrAlSiNb coating, which is prepared by ion beam-assisted magnetron sputtering and includes the following steps:

[0007] S1. Etch the target and the substrate

[0008] The target is an equimolar FeCrAlSiNb target. Take an alloy substrate with a mirror-like surface and the target after pretreatment to remove surface contaminants, place them in the vacuum chamber of an ion beam composite magnetron sputtering deposition system, evacuate the vacuum chamber, and then introduce the working gas until the vacuum degree of the vacuum chamber reaches 0.8 - 1.0 Pa; adjust the DC target power of the FeCrAlSiNb target to 80 - 120 W, and etch the target for 20 - 30 min to remove impurities and oxides on the target surface;

[0009] After the target etching is completed, apply a pulsed bias voltage of -800 V to -1000 V on the substrate, with a duty cycle of 40 - 50%; adjust the ion source current to 0.5 - 0.6 A, with a duty cycle of 40 - 50%, and etch the substrate for 20 - 30 min;

[0010] S2. Deposit the FeCrAlSiNb high-entropy alloy coating

[0011] After step S1 is completed, keep the atmosphere and air pressure in the vacuum chamber unchanged, and deposit the FeCrAlSiNb high-entropy alloy coating using magnetron sputtering technology, with a DC sputtering power of 80 - 120 W and a deposition time of 8 - 12 h; obtain an alloy coating on the substrate surface;

[0012] S3. Annealing treatment

[0013] Perform atmospheric annealing treatment on the coating obtained in step S2 at 650 °C - 850 °C for 30 - 40 min.

[0014] Preferably, in step S1, take the alloy substrate and the target, place them in the vacuum chamber, first evacuate the vacuum chamber to 10 -3 ~10 -5 Pa, and then introduce the working gas with a flow rate of 90 - 110 SCCM. The working gas is argon.

[0015] Preferably, the pretreatment is: polish the substrate with sandpaper to obtain a smooth mirror-like surface, and then perform cleaning and drying for standby.

[0016] More preferably, the pretreatment is: polish the substrate successively with 600#, 1000#, and 3000# waterproof sandpapers to obtain a smooth mirror-like surface; then ultrasonically clean the substrate in acetone and alcohol to remove surface contaminants, and dry it with nitrogen for standby; the substrate is a zirconium alloy substrate.

[0017] Preferably, in step S1, the DC target power of the FeCrAlSiNb target is 100 W, a pulsed bias voltage of -800 V to -1000 V is applied to the substrate, and the duty cycle is 40 - 50%; the ion source current is adjusted to 0.5 - 0.6 A, the duty cycle is 40 - 50%, and the substrate is etched and cleaned for 20 - 30 min to clean the sample surface.

[0018] Preferably, in step S2, the DC sputtering power is 100 W and the deposition time is 10 h.

[0019] Preferably, in step S3, the atmospheric annealing time is 30 min.

[0020] The second aspect of the present invention provides a high-temperature oxidation-resistant FeCrAlSiNb coating on the surface of a zirconium alloy cladding, which is prepared by using the preparation method described in any one of the above.

[0021] For the high-temperature oxidation-resistant FeCrAlSiNb coating on the surface of the zirconium alloy cladding, the composition of the FeCrAlSiNb coating obtained after annealing treatment is expressed as Fe x Cr y Al z Si m Nb n O p , where x, y, z, m, n, p are atomic ratios, 17 ≤ x ≤ 23, 16 ≤ y ≤ 20, 12 ≤ z ≤ 15, 14 ≤ m ≤ 17, 14 ≤ n ≤ 17, 11 ≤ p ≤ 23; the coating is a face-centered cubic lattice FCC structure.

[0022] Preferably, the coating thickness is 4.0 - 4.5 μm; the coating composition is expressed as Fe x Cr y Al z Si m Nb n O p , where x, y, z, m, n are atomic ratios, 17 ≤ x ≤ 18, 16 ≤ y ≤ 17, 14 ≤ z ≤ 15, 14 ≤ m ≤ 15, 14 ≤ n ≤ 15, 21.5 ≤ p ≤ 22.5.

[0023] The beneficial effects of the present invention are:

[0024] 1. The conventional core elements Fe, Cr, and Al in the coating are used to provide the oxidation resistance of the coating at high temperatures. The elements Si and Nb can promote the rapid formation of a surface protective oxide layer during the oxidation process. The annealing treatment at 650°C - 850°C can promote the redistribution of coating elements and improve the density of the coating. Moreover, the heat treatment can promote the reaction between Si and Zr to form a zirconium silicide diffusion layer with higher strength, overcoming problems such as the inability to rapidly form a continuous and dense oxide layer on the surface of the FeCrAl coating during high-temperature oxidation and the interdiffusion between the coating and the substrate to form a Fe-Zr eutectic, etc., and can meet the service performance requirements of the surface coating of the Zr alloy cladding tube under accident conditions.

[0025] 2. Si and Nb are selected to be added to the FeCrAl coating. Among them, Si can reduce the critical Al or Cr content when forming a continuous Al2O3 or Cr2O3 layer, that is, after adding Si, the coating can form a continuous Al2O3 or Cr2O3 layer at a lower Al or Cr content, reducing the formation difficulty of the Al2O3 and Cr2O3 layers; and the SiO2 particles formed in the early stage can serve as the nucleation sites for Al2O3 or Cr2O3, which is beneficial to the formation of a continuous Al2O3 or Cr2O3 layer; at high temperatures, Si can react with Zr to form a zirconium silicide diffusion layer with higher strength, which can significantly improve the bonding strength between the coating and the substrate and inhibit the interdiffusion of Fe-Zr elements. The addition of Nb can significantly improve the mechanical properties of the FeCrAl coating and promote the formation of a thick Al2O3 oxide film. During the preparation process of the high-entropy alloy coating, pores and cracks are easily generated due to rapid cooling or thermal stress, becoming the channels for the penetration of oxidation media.

[0026] 3. Before the formal deposition, pre-etching of the target can eliminate the oxide layer, adsorbed impurities, organic pollutants, etc. formed on the surface of the target due to exposure to the atmosphere, ensuring that the composition of the sputtered material is consistent with the target body. Pre-etching of the substrate can remove contaminants such as grease, oxides, and dust on the surface of the substrate, reduce the density of interface defects, and avoid the decrease in adhesion caused by interface contamination of the film; eliminate the gas molecules adsorbed on the surface layer of the substrate, reduce the formation of pores or bubbles during the film deposition process, and improve the density of the coating. At the same time, the roughening and activation of the substrate surface by ion bombardment can enhance the film-substrate bonding strength and improve the film uniformity.

[0027] 4. The pretreatment and coating deposition steps of the method of the present invention do not require external heating of the substrate and can be carried out at room temperature. Preparing the coating at room temperature can reduce thermal stress and avoid cracks or peeling caused by the mismatch of the thermal expansion coefficients between the coating and the substrate. The low-temperature deposition at room temperature can improve grain growth and form a finer grain structure, thereby improving the hardness and wear resistance of the coating. It can also avoid the performance degradation of the substrate material caused by thermal deformation, oxidation, etc. The equipment does not require a complex temperature control system, and at the same time, since there is no need for heating and cooling steps during the preparation process, the process debugging cycle is shortened.

[0028] 5. Annealing heat treatment at 650°C - 850°C can promote the diffusion and redistribution of elements inside the coating, fill the pores and heal the microcracks, thereby improving the density of the coating, and effectively improving the mechanical properties, oxidation resistance, etc. of the coating. Therefore, after heat treatment, the FeCrAlSiNb high-entropy alloy coating can have good high-temperature oxidation resistance while possessing the excellent mechanical properties of the HEAs coating, providing more choices for accident-tolerant nuclear fuel cladding materials.

[0029] 6. The preparation technology of the present invention has the advantages of simplicity, low cost, and large-area deposition. On the one hand, the introduction of Si and Nb elements promotes the rapid formation of a surface protective oxide layer, improving the oxidation resistance of the coating. On the other hand, the annealing heat treatment process in the present invention can promote the diffusion and redistribution of elements inside the coating, fill the pores existing in the coating preparation process and heal the microcracks, thereby improving the density of the coating. In the 1200°C high-temperature steam oxidation experiment, the FeCrAlSiNb high-entropy alloy coating inhibited the oxidation of the Zr alloy substrate and showed excellent high-temperature oxidation characteristics. The present invention has developed a new high-temperature oxidation-resistant high-entropy alloy coating.

[0030] 7. The method of the present invention uses single-target sputtering. The target is a single target made by uniformly melting 5 elements. Compared with the multi-target co-sputtering reported in the prior art, the process flow is simpler. Only a single target and a sputtering source are required, without the need for multi-target collaborative regulation, significantly simplifying the equipment configuration and the process parameter optimization process; the adjustment of process parameters is more convenient and accurate. By adjusting single variables such as sputtering power, gas pressure, and substrate bias voltage, the coating thickness, crystallinity, and stress state can be accurately controlled. In terms of the coating composition, when preparing the coating by single-target sputtering, the coating composition strictly depends on the target component, avoiding the element ratio fluctuation during multi-target co-sputtering and ensuring the compositional uniformity between batches. Description of the Drawings

[0031] Figure 1 (a) Cross-sectional SEM image and (b) XRD pattern of the FeCrAlSiNb high-entropy alloy coating prepared in Example 1.

[0032] Figure 2 Contact angle diagram of the FeCrAlSiNb high-entropy alloy coating prepared in Example 1.

[0033] Figure 3(a) Hardness and (b) elastic modulus of the FeCrAlSiNb high-entropy alloy coatings prepared in Examples 1-3 after atmospheric annealing. In the figure, Zr on the abscissa represents the Zr substrate control without coating preparation, 25 °C represents the control of the coating prepared at room temperature without high-temperature annealing, and 650 °C, 750 °C, and 850 °C represent the coatings prepared in Example 3, Example 2, and Example 1, respectively.

[0034] Figure 4 (a) Cross-sectional SEM image (arrow direction is the line scanning direction) and (b) EDS line scanning spectrum (the boxed area is the Si-Zr interdiffusion zone) of the FeCrAlSiNb high-entropy alloy coating prepared in Example 1 after atmospheric annealing.

[0035] Figure 5 (a) Cross-sectional SEM image of the FeCrAlSiNb annealed coating prepared in Example 1 after steam oxidation at 1200 °C and (b) XRD pattern.

[0036] Figure 6 Macromorphology of the specimen cross-section of the FeCrAlSiNb annealed coating prepared in Example 1 after steam oxidation at 1200 °C. Detailed implementation manners

[0037] The present invention will be further described below in conjunction with examples, but the present invention is not limited thereby.

[0038] The experimental methods in the following examples are all conventional methods unless otherwise specified.

[0039] In Examples 1-3 of the present invention, the substrate sample is a commercially available Zr-4 alloy (standard composition: Zr-98.2%, Sn-1.5%, Fe-0.2%, Cr-0.1%), which is cut into a size of 10 mm * 10 mm * 2 mm for experiments; the equimolar FeCrAlSiNb target is obtained commercially.

[0040] The coating equipment is an ion beam composite magnetron sputtering deposition system, and the high-temperature oxidation-resistant FeCrAlSiNb high-entropy alloy coating of the present invention is prepared by using ion beam-assisted magnetron sputtering.

[0041] Example 1:

[0042] The preparation of the high-temperature oxidation-resistant FeCrAlSiNb high-entropy alloy coating of the present invention is carried out according to the following steps:

[0043] 1) Cleaning the substrate: The Zr-4 substrate was polished successively with 600#, 1000# and 3000# waterproof sandpapers to remove the scratches on the substrate and obtain a smooth mirror-like surface. Subsequently, the substrate was ultrasonically cleaned continuously in acetone and alcohol for 15 min to remove surface contaminants, and then dried with nitrogen for standby.

[0044] 2) Pretreatment (etching the target and the substrate): An equimolar FeCrAlSiNb target (99.95%) was placed on the cathode target seat, and the dried substrate was placed on the sample stage. The vacuum chamber was evacuated to 10 -3 Pa, and then argon was introduced with a flow rate of 105 SCCM, and the vacuum degree of the vacuum chamber was maintained at about 0.8 Pa. The power of the FeCrAlSiNb target was adjusted to DC (direct current) 100 W, and the target was etched for 20 min to remove impurities and oxides on the target surface. After the target etching was completed, a pulsed bias voltage of -800 V with a duty cycle of 50% was applied to the substrate, the ion source current was adjusted to 0.5 A with a duty cycle of 50%, and the substrate was sputter-etched for 20 min to clean the sample surface.

[0045] 3) Depositing the FeCrAlSiNb high-entropy alloy coating: After the pretreatment was completed, the atmosphere and air pressure in the vacuum chamber were kept unchanged. The deposition power of the FeCrAlSiNb high-entropy alloy coating was DC (direct current) 100 W, and the deposition time was 600 min. A FeCrAlSiNb high-entropy alloy metal coating was obtained on the substrate surface. During the preparation process, the substrate was not externally heated and could be carried out at room temperature.

[0046] 4) The FeCrAlSiNb high-entropy alloy metal coating was subjected to an atmospheric annealing treatment at 850 °C for 30 min.

[0047] The obtained high-temperature oxidation-resistant FeCrAlSiNb high-entropy alloy coating had a thickness of 4.2 μm, and this layer contained elements of Fe, Cr, Al, Si, and Nb.

[0048] Example 2:

[0049] The preparation of the high-temperature oxidation-resistant FeCrAlSiNb high-entropy alloy coating of the present invention was carried out according to the following steps:

[0050] 1) Cleaning the substrate: The Zr-4 substrate was polished successively with 600#, 1000# and 3000# waterproof sandpapers to remove the scratches on the substrate and obtain a smooth mirror-like surface. Subsequently, the substrate was ultrasonically cleaned continuously in acetone and alcohol for 20 min to remove surface contaminants, and then dried with nitrogen for standby.

[0051] 2) Pretreatment (etching the target and the substrate): Place the equimolar FeCrAlSiNb target (99.95%) and the dried substrate at the corresponding positions in the vacuum chamber. Evacuate the vacuum chamber to 10 -4 Pa, then introduce argon with a flow rate of 105 SCCM and keep the vacuum degree of the vacuum chamber at about 0.9 Pa. Adjust the power of the FeCrAlSiNb target to DC (direct current) 100 W and etch the target for 25 min to remove impurities and oxides on the target surface. After the target etching is completed, apply a pulsed bias voltage of -900 V to the substrate with a duty cycle of 45%; adjust the ion source current to 0.55 A with a duty cycle of 45% and etch and clean the substrate for 25 min to clean the sample surface.

[0052] 3) Deposit the FeCrAlSiNb high-entropy alloy coating: After the pretreatment is completed, keep the atmosphere and air pressure in the vacuum chamber unchanged, with the vacuum degree of the vacuum chamber being 0.9 Pa, the deposition power of the FeCrAlSiNb high-entropy alloy coating being DC (direct current) 100 W, and the deposition time being 600 min. Obtain a FeCrAlSiNb high-entropy alloy metal coating on the substrate surface. During the preparation process, the substrate has no external heating.

[0053] 4) Perform an atmospheric annealing treatment on the FeCrAlSiNb high-entropy alloy metal coating at 750 °C for 30 min.

[0054] The obtained high-temperature oxidation-resistant FeCrAlSiNb high-entropy alloy coating has a thickness of 4.2 μm, and this layer contains elements Fe, Cr, Al, Si, and Nb.

[0055] Example 3:

[0056] Preparation of the high-temperature oxidation-resistant FeCrAlSiNb high-entropy alloy coating, operate according to the following steps:

[0057] 1) Clean the substrate: Polish the Zr-4 substrate successively with 600#, 1000#, and 3000# waterproof sandpapers to remove scratches on the substrate and obtain a smooth mirror-like surface. Subsequently, ultrasonically clean the substrate in acetone and alcohol continuously for 20 min to remove surface contaminants, and dry it with nitrogen for standby.

[0058] 2) Pretreatment (etching the target and the substrate): Place the equimolar FeCrAlSiNb target (99.95%) and the dried substrate at the corresponding positions in the vacuum chamber. Evacuate the vacuum chamber to 10 -5Pa, and then argon gas was introduced with a flow rate of 105 SCCM while maintaining the vacuum degree of the vacuum chamber at about 1.0 Pa. The power of the FeCrAlSiNb target was adjusted to DC (direct current) 100 W, and the target was etched for 30 min to remove impurities and oxides on the target surface. After the target etching was completed, a pulsed bias voltage of -1000 V with a duty cycle of 40% was applied to the substrate; the ion source current was adjusted to 0.6 A with a duty cycle of 40%, and the substrate was etched and cleaned for 20 min to clean the sample surface.

[0059] 3) Depositing the FeCrAlSiNb high-entropy alloy coating: After the pretreatment was completed, the atmosphere and air pressure in the vacuum chamber were kept unchanged, the vacuum degree of the vacuum chamber was 1.0 Pa, the deposition power of the FeCrAlSiNb high-entropy alloy coating was DC (direct current) 100 W, and the deposition time was 600 min. A FeCrAlSiNb high-entropy alloy metal coating was obtained on the substrate surface. During the preparation process, there was no external heating of the substrate.

[0060] 4) Performing an atmospheric annealing treatment on the FeCrAlSiNb high-entropy alloy metal coating at 650 °C for 30 min.

[0061] The obtained high-temperature oxidation-resistant FeCrAlSiNb high-entropy alloy coating had a thickness of 4.2 μm, and this layer contained elements Fe, Cr, Al, Si, and Nb.

[0062] The element compositions of the coatings prepared in Examples 1 - 3 before (Table 1) and after (Table 2) the annealing treatment in step 4) were analyzed using an energy-dispersive X-ray spectrometer (EDAX).

[0063] Table 1 shows the element compositions of each example

[0064]

[0065] Table 2 shows the element compositions of each example after heat treatment

[0066]

[0067] The high-temperature oxidation-resistant FeCrAlSiNb high-entropy alloy coating prepared by the present invention using ion beam-assisted magnetron sputtering (see Figure 1)The surface is flat and smooth, the cross-section of the coating is dense, and it adheres well to the substrate. The prepared coating structure is a face-centered cubic lattice (FCC), and the FCC structure has good thermal stability. Compared with the amorphous structure, due to the highly ordered arrangement and close-packed atomic arrangement in the FCC structure, the atoms are more closely bonded, the diffusion path is longer, and higher energy is required for movement. This makes the coating less likely to undergo structural changes at high temperatures, thus maintaining its strength. In addition, the high symmetry and multiple slip systems of FCC may help to disperse stress at high temperatures, reduce coating cracking caused by local deformation, and ensure the integrity of the coating during the oxidation process.

[0068] The hydrophobic angle of the FeCrAlSiNb high-entropy alloy coating of the present invention is greater than 90°, and it has certain hydrophobicity (see Figure 2 ).

[0069] Oxidation products are generated on the surface of the coating after annealing treatment, so the O element is detected in the annealed coating. The annealing treatment effectively improves the hardness and elastic modulus of the coating, and the hardness and elastic modulus of the coating gradually increase with the increase of the annealing temperature (see Figure 3 ): Figure 3 In it, Zr on the abscissa represents the Zr substrate control without the prepared coating, 25°C represents the control of the prepared coating sample at room temperature without high-temperature annealing, and 650°C, 750°C, and 850°C respectively represent the coatings prepared in Example 3, Example 2, and Example 1. From Figure 3 It can be seen that compared with the Zr substrate without the prepared coating or the control of the coating sample prepared at room temperature, after depositing the coating and performing air annealing at 650°C, 750°C, and 850°C for 30 min, the hardness and elastic modulus of the product have been significantly improved, and the improvement is the highest after annealing at 850°C. It can be seen that performing air annealing at 650°C to 850°C after depositing the coating can significantly improve the mechanical properties of the product. Analyzing the reasons, on the one hand, it is related to the formation of the high-hardness Al2O3 and Cr2O3 layers on the surface, and on the other hand, the high-temperature annealing heat treatment promotes the diffusion and redistribution of elements inside the coating, fills the pores and heals the microcracks, thereby improving the density of the coating, and effectively improving the mechanical properties of the coating.

[0070] FeCrAlSiNb high-entropy alloy coating after annealing (see Figure 4 ): Figure 4 a is the cross-section SEM morphology diagram of the FeCrAlSiNb coating after annealing at 850°C, Figure 4 b is the coating cross-section EDS line scan of the FeCrAlSiNb coating after annealing at 850°C. From Figure 4It can be seen that a relatively obvious Si-Zr diffusion zone is formed between the coating and the substrate after annealing treatment, and a complete and continuous thin oxide layer is formed on the surface of the coating. The existence of the Si-Zr diffusion layer can enhance the bonding between the coating and the substrate, prevent the coating from peeling off during the oxidation process, and also inhibit the interdiffusion between the coating and the substrate at high temperatures. In a high-temperature steam environment, the existence of the oxide layer on the surface of the annealed coating can effectively delay the rapid inward diffusion of O elements at the initial stage of steam oxidation, providing time for the formation of a thicker protective oxide layer.

[0071] The Zr alloy specimen with an FeCrAlSiNb high-entropy alloy coating prepared in Example 1 after heat treatment was placed in a high-temperature steam simulation accident condition at 1200 °C for 30 min of oxidation test, and the test results are as Figure 5 shown. It can be seen from Figure 5 that the FeCrAlSiNb coating has good thermal stability, still maintains the FCC structure after steam oxidation at 1200 °C, a dense protective oxide film is formed on the surface of the FeCrAlSiNb coating, and the residual thickness of the FeCrAlSiNb high-entropy alloy coating is about 4 μm. Figure 6 It shows that the coated side of the Zr alloy substrate remains intact and is not oxidized; while there is an oxide layer with a thickness of more than 150 μm on the uncoated side, indicating that the FeCrAlSiNb coating has good high-temperature steam oxidation resistance.

Claims

1. A method for preparing a high-temperature oxidation-resistant FeCrAlSiNb coating, characterized in that: Preparation by ion beam assisted magnetron sputtering includes the following steps: S1. Etching target and substrate The target material is an equimolar FeCrAlSiNb target. The alloy substrate and the target material having a mirror-like surface after pretreatment to remove surface pollutants are placed in a vacuum chamber of an ion beam composite magnetron sputtering deposition system. The vacuum chamber is evacuated, and then a working gas is introduced until the vacuum degree of the vacuum chamber is 0.8-1.0 Pa. The DC target power of the FeCrAlSiNb target is adjusted to 80-120 W, and the target material is etched for 20-30 minutes to remove impurities and oxides on the surface of the target material. After the target material is etched, a pulse bias voltage of -800V to -1000V is applied to the substrate, with a duty cycle of 40 to 50%; the ion source current is adjusted to 0.5 to 0.6A, with a duty cycle of 40 to 50%, and the substrate is etched for 20 to 30 minutes; S2. Deposition of FeCrAlSiNb high entropy alloy coating After step S1 is completed, the atmosphere and pressure of the vacuum chamber are kept unchanged, and the FeCrAlSiNb high entropy alloy coating is deposited by using magnetron sputtering technology, the DC sputtering power is 80 to 120 W, and the deposition time is 8 to 12 hours; and the alloy coating is obtained on the surface of the substrate; S3, annealing The coating obtained in step S2 is subjected to an atmospheric annealing treatment at 650° C. to 850° C. for 30 to 40 minutes.

2. The preparation method according to claim 1, characterized in that: In step S1, the alloy substrate and the target are placed in a vacuum chamber, and the vacuum chamber is evacuated to 10 -3 ~10 -5 Pa, and then the working gas is introduced with a flow rate of 90-110 SCCM, and the working gas is argon.

3. The preparation method according to claim 1, characterized in that: The pretreatment is as follows: grinding the substrate with sandpaper to obtain a smooth mirror-like surface, and then cleaning and drying it for later use.

4. The preparation method according to claim 3, characterized in that: The pretreatment is as follows: polishing the substrate with 600#, 1000# and 3000# waterproof sandpaper in sequence to obtain a smooth mirror-like surface; then ultrasonically cleaning the substrate in acetone and alcohol to remove surface pollutants, and drying with nitrogen for later use; the substrate is a zirconium alloy substrate.

5. The preparation method according to claim 1, characterized in that: In step S1, the DC target power of the FeCrAlSiNb target is 100W, a pulse bias voltage of -800V to -1000V is applied to the substrate, and the duty cycle is 40-50%. The ion source current is adjusted to 0.5-0.6A, and the duty cycle is 40-50%, and the substrate is etched and cleaned for 20-30 minutes to clean the sample surface.

6. The preparation method according to claim 1, characterized in that: In step S2, the DC sputtering power is 100 W and the deposition time is 10 h.

7. The preparation method according to claim 1, characterized in that: In step S3, the atmospheric annealing time is 30 minutes.

8. A high temperature oxidation resistant FeCrAlSiNb coating on the surface of a zirconium alloy cladding, characterized in that: The preparation method is described in any one of claims 1 to 7.

9. The high temperature oxidation resistant FeCrAlSiNb coating on the surface of the zirconium alloy cladding according to claim 8, characterized in that: The composition of the FeCrAlSiNb coating obtained after annealing is expressed as Fe x Cr y Al z Si m Nb n O p , where x, y, z, m, n, and p are atomic ratios, 17≤x≤23, 16≤y≤20, 12≤z≤15, 14≤m≤17, 14≤n≤17, and 11≤p≤23; the coating has a face-centered cubic lattice FCC structure.

10. The high temperature oxidation resistant FeCrAlSiNb coating on the surface of the zirconium alloy cladding according to claim 9, characterized in that: The coating thickness is 4.0~4.5Um; the coating composition is expressed as Fe x Cr y Al z Si m Nb n O p , where x, y, z, m, n are atomic ratios, 17≤x≤18, 16≤y≤17, 14≤z≤15, 14≤m≤15, 14≤n≤15, 21.5≤p≤22.5.